Chemical properties of thermoplastic starch from Tacca Leonpetaloides: article - Zulfakar, Amirul Aiman; Ismail, Kamariah Noor (2019)
Environmental problem regarding plastic waste has always posed a threat to our environment. Conventional plastic are unable to be decompose biologically as it chemical structure are consist of polymer bond which are very stable and strong. Thus, the ideas of Thermoplastic starch are being suggested to be research in solving the environmental issue. The suggested starch being used in this research is Tacca Leonpetaloides. Tacca Leonpetaloides can be obtained commonly in the South East Asia region. Thus, the research are more focusing on the usage of Tacca starch into producing Thermoplastic Starch which are different from the conventional plastic used in term of chemical properties. Thus, these researches are focusing on the thermal decomposition. The component of the Thermoplastic Starch used is made from the combination of Polypropylene with Tacca Starch powder and produce it in film condition. From the study , the amount of starch used in the TPS film affect the performance of the thermal decomposition as the amount of starch increase , the thermal decomposition are much more easier to be decomposed whereas the polypropylene are much more hard to be decomposed respectively. The water absorption capabilities of Thermoplastic are the highest at starch 20% to polypropylene of the thermoplastic ratio with 0.263% of weight increase after being immerse in water for 72 hour.